The Effect of the Jigsaw Learning Method and Initial Ability on the Learning Outcomes of Automotive Engineering Students - Frandiska Eltian; Amat Mukhadis; Paryono Paryono (Faculty of Engineering, Universitas Negeri Yogyakarta, 2017)
The purposes of this study were testing the significant differences of learning outcomes between group of students who were treated with jigsaw learning method and those who were treated with the conventional method with considering the students’ initial ability. This study was designed with a quasi-experimental non-equivalent control group design. The sampling technique used random assignment. The sample consisted of 63 students. A test was used to measure the initial ability and learning result of the students. The data were analyzed by using a two way Anova method. The results were: (1) the learning outcomes of students in the subject of electronic ignition system maintenance with jigsaw learning method was better than the students treated with conventional learning; (2) based on the learning outcomes in the subject of electronic ignition system maintenance, a group of students with high initial ability was better than a group of students with medium and low initial ability; (3) there was not interaction between learning method and initial ability towards learning outcomes students. It means, the excellence of jigsaw learning and conventional learning in improving learning outcomes for the subject of electronic ignition system maintenance do not depend on students' initial ability.